Trends in the co-use of alcohol and tobacco among Japanese adolescents: periodical nationwide cross-sectional surveys 1996–2017. Issue 8 (4th August 2021) - Fujii, Maya; Kuwabara, Yuki; Kinjo, Aya; Imamoto, Aya; Jike, Maki; Otsuka, Yuichiro; Itani, Osamu; Kaneita, Yoshitaka; Minobe, Ruriko; Maesato, Hitoshi; Higuchi, Susumu; Yoshimoto, Hisashi; et al.
Abstract : Objectives: This study aimed to assess trends in the prevalence of alcohol use depending on smoking behaviours and that of smoking depending on drinking behaviours among Japanese adolescents. Design: This was a retrospective study using Japanese school-based nationwide surveys conducted between 1996 and 2017. Setting: Surveyed schools, both junior and senior high schools, considered representative of the entire Japanese population, were sampled randomly. Participants: We enrolled 11 584–64 152 students from 179 to 103 schools yearly. They completed a self-reported and anonymous questionnaire on smoking and drinking behaviour. Results: Since 1996, the prevalence of alcohol use and smoking among adolescents decreased in each survey (p<0.01). The prevalence of alcohol use in the non-smokers group was 29.0% in 1996 and 4.0% in 2017, and in the smokers group, it was 73.3% in 1996 and 57.4% in 2017. The reduction rate (the difference in prevalence between 1996 and 2017 divided by the prevalence in 1996) was 0.86 in the non-smokers group and 0.22 in the smokers group. The prevalence of smoking in the non-drinkers group was 6.7% in 1996 and 0.7% in 2017, while that in the drinkers group was 32.5% in 1996 and 18.9% in 2017. The reduction rate was 0.90 in the non-drinkers group and 0.42 in the drinkers group. Therefore, downward trends differed among the groups. In a subanalysis of senior high school students, we divided students into three groups according to their intention to pursue further education. Between 1996 and 2017, there was a consistent difference in the prevalence of alcohol use and smoking among these groups. Conclusions: Alcohol use and smoking among Japanese adolescents seem to have reduced. However, certain groups showed poor improvements, and health risk behaviour disparity exists, which may widen further. We need to focus on high-risk groups and implement appropriate measures or interventions accordingly.